Determination of phosphatidylethanol 16:0/18:1 in whole blood by 96‐well supported liquid extraction and UHPLC‐MS/MS. Issue 1 (25th July 2018) - Berg, Thomas; Eliassen, Elin; Jørgenrud, Benedicte; Kabashi, Saranda; Petukhov, Alexey; Bogstrand, Stig Tore
Abstract : Background: Phosphatidylethanols (PEths) are specific, direct alcohol biomarkers that can be determined in human blood to distinguish between heavy and social drinking. PEth 16:0/18:1 is among the most predominant PEth homologues in human blood. The aim of the study was to develop a high throughput and sensitive UHPLC‐MS/MS method for the determination of PEth 16:0/18:1 in whole blood. Methods: Whole blood samples were prepared by 96‐well supported liquid extraction (SLE). Extracted samples were analyzed for PEth 16:0/18:1 by reversed phase UHPLC‐MS/MS. Results: The developed UHPLC‐MS/MS method was fully validated in whole blood with PEth 16:0/18:1‐D5 as internal standard. Intermediate precision and intermediate accuracy were within ≤± 12% and ≤± 17%, respectively, at PEth 16:0/18:1 concentrations of 1.4‐2112 ng/mL (2.0‐3004 nmol/L). Limit of quantification (LOQ) was 1.7 ng/mL (2.4 nmol/L). Conclusion: For the first time, 96‐well SLE was used for preparation of a PEth homologue in biological samples. A mixture of tert‐butyl methyl ether and 2‐propanol (5:1, v:v) was chosen as organic eluent based on an evaluation of extraction recovery, purity of extracts, and evaporation time. The developed UHPLC‐MS/MS method can be used for high throughput analyses and sensitive determinations of PEth 16:0/18:1 in whole blood.